1986
DOI: 10.1111/j.1751-1097.1986.tb05595.x
|View full text |Cite
|
Sign up to set email alerts
|

IN SITU HYDROGEN PEROXIDE PRODUCTION MAY ACCOUNT FOR A PORTION OF NUV (300–400 nm) INACTIVATION OF STATIONARY PHASE Escherichia coli

Abstract: Abstract— Pre‐irradiation of stationary phase cells of Escherichia coli K‐12 with broadband near‐UV radiation potentiates the lethal effects of subsequent exposure to near‐UV radiation plus hydrogen peroxide. Identical fluences failed to modulate killing due to far‐UV radiation. These data indicate that biologically revelant levels of hydrogen peroxide may be generated in situ upon the near‐UV irradiation of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…Although significant H 2 O 2 levels have never been measured in micro-organisms exposed to UVA (Hartman, 1986;Kramer & Ames, 1987), our data employing ROS scavengers and reporter strains support the hypothesis that H 2 O 2 is a major product of exposure to lethal UVA doses (Tyrrell, 1985;Hartman, 1986;Kramer & Ames, 1987;Khaengraeng & Reed, 2005). In addition, it is demonstrated that induction of katA and katB depends, at least in part, on the H 2 O 2 levels generated by UVA exposure, suggesting an OxyR-mediated response.…”
Section: Discussionsupporting
confidence: 67%
“…Although significant H 2 O 2 levels have never been measured in micro-organisms exposed to UVA (Hartman, 1986;Kramer & Ames, 1987), our data employing ROS scavengers and reporter strains support the hypothesis that H 2 O 2 is a major product of exposure to lethal UVA doses (Tyrrell, 1985;Hartman, 1986;Kramer & Ames, 1987;Khaengraeng & Reed, 2005). In addition, it is demonstrated that induction of katA and katB depends, at least in part, on the H 2 O 2 levels generated by UVA exposure, suggesting an OxyR-mediated response.…”
Section: Discussionsupporting
confidence: 67%
“…Recently, Leowen and his colleagues have described mutants which are defective in catalase activity (21)(22)(23). In this paper, we present evidence that lesions in the katF gene, but not the katE or katG gene, result in sensitivity to broad-spectrum NUV as well as to 14 SAMMARTANO ET AL. Cells were grown at 37°C with shaking in sidearm flasks (Belco) containing 50 ml of LB broth to stationary phase as described previously (37,38).…”
mentioning
confidence: 94%
“…Peak et al (1987) have shown that a significant amount of DNA damage due to near-UV occurs by single-stand breaks. Near-UV radiation is also known to produce reactive oxygen species such as superoxide anion, singlet oxygen and hydrogen peroxide in bacteria (Webb, 1977;Hartman, 1986) and mammalian cells (Danpure and Tyrrell, 1976). However, the role of these photoproducts in UV carcinogenesis is unknown.…”
Section: Correlation Of Dna Photoproducts To Cell Lethality Mutationmentioning
confidence: 99%